Redesain Kursi Roda Portable untuk Lansia dengan Pendekatan Participatory Ergonomic - Rahmat Nopriyansa; Ch. Desi Kusmindari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to redesign portable wheelchairs for the elderly at RS Charitas KM 7 Palembang using a participatory ergonomic approach. At the age of 60 and above, the elderly are vulnerable to diseases affecting mobility, requiring ergonomic assistive devices such as wheelchairs. The research was conducted from May to June 2024 using primary data collection through questionnaires given to elderly wheelchair users at RS Charitas and secondary data from relevant literature. Validity and reliability tests of the questionnaire were conducted using SPSS version 25. The results showed that the functional characteristics of the wheelchair (standard shape, adjustable and foldable, additional activity functions, footrests, flat surfaces, metal handles, and easy to clean) significantly affect the comfort and ease of use of the wheelchair. The regression model used is quite good at explaining variations in the dependent variable, although there are other factors outside the model that also influence the comfort and ease of use of the wheelchair.